Found Footage Dracula: Reflections on an audiovisual realization exercise - Cánepa, Laura Loguercio; Borges Monteiro, Juliana Cristina (Mediaciones Sociales, 2018)
Found footage fiction films are a massive phenomenon of audiovisual production and consumption, especially in fantasy and horror genres. A fundamental feature of these films is the intradiegetic camera - that is, their narratives are constructed through records made by devices that belongs to the diegese. In this paper, we observe this procedure from what we consider as one of its origins: the epistolary fiction, based on fictional records of letters, reports, journals and other documents. In this essay, we will present the results of a practical research developed in 2017, in which a class of undergraduate students of the Audiovisual Language of the Universidade Anhembi Morumbi adapted, in the found footage fiction style, scenes described by five different intradiegetic narrators of Bram Stoker’s novel Dracula (1897). Our goal is to analyze the stylistic characteristics of the scenes performed by the students, in order to expand our understanding about the creative challenges and experiences provided by found footage fiction.